Antiviral therapy of orthopoxvirus infection - Kern, Earl R.; Prichard, Mark N. (Henry Stewart Talks, 2011)
Orthopoxviruses that infect humans, Effective antiviral therapies, Development of CMX001, Development of ST-246, Mechanism of action of drugs